2014
DOI: 10.4103/0973-1482.137929
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gingival biopsies in the Gujarati population: A retrospective study

Abstract: It is difficult to compare studies carried out in various countries due to differences in people's attitudes toward oral health and the accessibility of various population groups to biopsy services. Nevertheless, this study has provided some information about the frequency and distribution of biopsied gingival lesions in the Gujarati population over a period of five years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 10 publications
14
16
0
Order By: Relevance
“…The present study demonstrated that the overall distribution of lesions was similar to that observed in other studies [6][7][8]. The vestibule of the mouth and the lips are exposed to harmful factors, such as biting, chronic irritation, mechanical and thermal injuries and, in the case of lips, also solar radiation.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The present study demonstrated that the overall distribution of lesions was similar to that observed in other studies [6][7][8]. The vestibule of the mouth and the lips are exposed to harmful factors, such as biting, chronic irritation, mechanical and thermal injuries and, in the case of lips, also solar radiation.…”
Section: Discussionsupporting
confidence: 89%
“…Most of the oral lesions, with the exception of salivary gland pathologies, occurred after the age of 45, which confirms the results obtained in other studies [6][7][8]. These results may be associated with the accumulation of all harmful habits and parafunctions and iatrogenic factors in the oral cavity.…”
Section: Discussionsupporting
confidence: 89%
“…Malignant neoplasms of the gingiva accounted for 7.6% of the total number of cases, which was higher than reported in the study by Manjunatha et al ( 9 ) but lower than reported in other epidemiologic data ( 5 , 8 , 10 ) and is in accordance with reports by Mario Carbone et al ( 11 ). OSCC was the only malignant neoplasm reported in gingival biopsy specimens in this study, which was in accordance with the results of many other studies ( 5 , 8 , 11 ).…”
Section: Discussionsupporting
confidence: 87%
“…Thus, this method can be recommended to treat pathological conditions involving bacterial etiology such as peri-implantitis and periodontal diseases. Although the expressive good results as an antimicrobial agent, further studies are needed to prove its efficiency in cases of PGCG around dental implants [7, 11, 2022].…”
Section: Discussionmentioning
confidence: 99%